Legal Protection of Semar Pouch (Nepenthes): Efforts to Increase Enviromental Conservation: Perlindungan Hukum terhadap Tumbuhan Kantong Semar (Nepenthes) : Upaya Meningkatkan Konservasi Lingkungan Hidup - Budiani, Revalio Putra; Rosnawati, Emy (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Indonesia holds rich biodiversity including carnivorous Nepenthes species that face threats from overexploitation and habitat loss. Specific background: Illegal collection and trade of Nepenthes have reduced wild populations and triggered legal responses at national and international levels. Knowledge gap: Existing literature emphasizes botanical and distributional studies but lacks focused legal analysis of protection mechanisms and enforcement outcomes. Aims: This study analyzes Indonesia’s legal framework and enforcement actions concerning Nepenthes to assess the adequacy of preventive and repressive protections. Results: Normative analysis of statutes, ministerial regulations, and documented enforcement cases reveals clear legal prohibitions and prescribed sanctions, yet enforcement variability and awareness gaps persist. Novelty: The paper synthesizes statutory provisions with recent case evidence to highlight implementation gaps in legal protection for Nepenthes. Implications: Findings suggest targeted policy improvements—strengthened monitoring, community engagement, and clearer species-specific guidance—to enhance conservation and legal compliance. Highlights: Statutory protections and ministerial listing for 59 Nepenthes species. Documented enforcement case linking illegal trade to cross-border buyers. Gap between legal provisions and practical enforcement outcomes. Keywords: Nepenthes, Legal Protection, Conservation Law, Illegal Trade, Indonesia